Additional posterior wall isolation is associated with gastric hypomotility in catheter ablation of atrial fibrillation. (1st March 2021) - Oikawa, Jun; Fukaya, Hidehira; Wada, Takuya; Horiguchi, Ai; Kishihara, Jun; Satoh, Akira; Saito, Daiki; Sato, Tetsuro; Matsuura, Gen; Arakawa, Yuki; Kobayashi, Shuhei; Shirakawa, Yuki; et al.
Abstract: Background: Gastric hypomotility (GH) is a possible complication of catheter ablation (CA) for atrial fibrillation (AF). However, it is unclear which factors are associated with GH. We sought to elucidate the relationship between the CA procedure and GH. Methods: The study population consisted of 254 patients who underwent CA for AF from November 2017 to October 2018. Finally, 119 patients were enrolled and divided into two groups: with or without GH (GH or non-GH groups). To evaluate the association with GH, the clinical backgrounds and procedure characteristics of the radiofrequency CA (RFCA) were compared between the two groups. Results: The median age was 69 years old with 34% of female. GH were observed in 27.7% of patients who underwent RFCA, which was significantly higher than that in the cohort of patients who underwent esophago-gastro-duodenoscopy during the same time period (1.9%: 151 in 8063 patients, p < 0.0001). According to the detailed RFCA procedure, additional posterior wall isolation with pulmonary vein isolation (PVI) had a higher prevalence of GH than that with only PVI (54.8% vs. 18.2%; odds ratio 5.46, 95%CI 2.24–13.32, p = 0.0002). After an adjustment using a multivariate logistic analysis, a posterior wall isolation with the PVI was identified as the only independent predictor for GH (odds ratio 5.01, 95%CI 1.94–13.43, p = 0.0009). Conclusions: Additional posterior wall isolation with PVI was associated with gastric hypomotility. Highlights: Gastric hypomotility (GH) is an important complication during AF ablation. We evaluated the incidence of GH after the index catheter ablation (CA). The GH was highly observed after the CA than general populations (27.7% vs. 1.9%). Additional posterior wall isolation was the independent risk factor for GH.